Inovasi Alat Pengering Tepat Guna: Desain Oven Multi-Fungsi untuk Mendorong Standarisasi dan Daya Saing Produk UMKM - Sundari, Susanti; Syahputra, Muhammad Reyhan; Suwarni, Putri Endah; Putra, Febriyansyah; Pratama, Very Zota; Nashiruddin, Muhammad; Andrian, Andi (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The main challenge for SMEs in the agro-industry sector is the low efficiency and product quality inconsistency resulting from conventional, weather-dependent drying methods. This study aims to design and verify an optimized multifunctional hybrid dryer oven model to support quality standardization and productivity in micro and small-scale settings.The quantitative approach utilizes the benchmarking method, focusing on developing a design that is more efficient and user-friendly (ergonomic) compared to existing models. The research successfully developed a hybrid cabinet oven with a practical capacity of 15–25 kg. Technically, the oven demonstrates superior performance: It uses a low-power energy combination of LPG and electricity (250 Watts), providing a cost-effective solution for energy efficiency;  the construction utilizes stainless steel material, ensuring durability, corrosion resistance, and compliance with hygiene standards (GMP); and functional verification confirmed the achievement of temperature stability and precision (ranging from 50°C to 100°C) via a thermal control system. This enables measurable drying processes within 120–180 minutes, significantly minimizing moisture variation. With an estimated production cost of Rp4,790,000, the oven is proven to be economically viable and highly potential for widespread adoption. This innovation substantially contributes to improving product quality and operational independence for local SMEs. Keywords: Benchmarking, Dryer Oven, Multifunctional, Quality Standardization, SMEs.